The Constitutionality of Notaries Honorary Assembly in the Enforcement of the Notary Ethics Code - Sulistyowati Sulistyowati; Umar Ma’ruf; Deva Rita (Jurnal Akta, 2022)
In general, Notaries are regulated in Act No. 30 of 2004 concerning the Position of Notary and Act No. 2 of 2014 concerning amendments to Act No. 30 of 2004 concerning the Position of Notary. A notary, in this case, may also double as a Land Deed Making Officer. The research used normative juridical methods with descriptive analytics. Prioritizing secondary data, namely literature studies, verdicts, books, and others, as the primary data. Indonesia, as a country of law, of course, everything has been regulated by regulations. This applies to all sectors and professions in Indonesia, including notarial matters. The Notary Profession is a legal profession that is entirely in demand. The position of a Notary is considered a noble profession, but there are still notaries who make mistakes or are negligent in carrying out their positions. Therefore, an institution is required that carries out supervision of a Notary. The institution is now known as the Honorary Assembly of Notaries. However, the existence of the Notary Honorary Assembly has not entirely caused trust in the community because it is still considered to cover up the mistakes of notaries who have harmed the community in carrying out their duties. The recruitment process that has not been transparent and involves the public may be one of the causes of the lack of such trust. So, in this case, the Notary Honorary Assembly must update its recruitment pattern.